Pengembangan Aplikasi Reinforcement Dalam Meningkatkan Perilaku Disiplin Guru dan Siswa Madrasah - Adawiyah, Robiatul (STAI Nurul Huda Kapongan Situbondo, 2020)
In the digital age, humans need tools to support increased disciplinary behavior. The purpose of the study, analyzing the need for tools, making based on needs, and applying tools (application reinforcement) to determine the impact of increasing disciplinary behavior of teachers and students of MI Perwanida Blitar. Research using R&D with ADDIE design models, product tests use pre-experimental designs with one group pretest-postets design. Samples by purposive technique. And analysis uses collected data that is descriptive qualitative and quantitative.